Role of Early Clinical Exposure in Medical Education: Effectiveness of Its Transition from Onsite to Online Sessions during the Pandemic - Shobha C Ramachandra; Swetha N Kempegowda; Kusuma K Shivashankar; Abhijith Devaraju; Suma M Nataraj; Akila Prashant (Indian Journal of Medical Biochemistry)
Introduction: We implemented online early clinical exposure (ECE) for medical undergraduate students during the pandemic and analyzed their feedback to assess the effectiveness of the session. Materials and methods: An online ECE on “Inborn Errors of Metabolism (IEM) and the Significance of Newborn Screening (NBS)” was scheduled, during which the participants were provided with information pertaining to the prevalence, morbidity, mortality, significance of NBS, and available treatment modalities that are currently accessible. Four case scenarios, which were developed in collaboration with clinicians, were discussed with the students. The students were divided into smaller groups, with each group being supervised by a faculty member. The feedback obtained from the students, using a five-point Likert scale, was subjected to analysis. Results: Around 87.5% of the total student population, specifically 175 out of 200 students, were actively engaged in the 4-hour session. Furthermore, a total of 152 students willingly participated in the questionnaire survey. The content validity ratio (CVR) and content validity index (CVI) yielded scores exceeding 0.95 and 0.86, respectively. Additionally, Cronbach’s alpha was found to be 0.95. The majority of the students demonstrated the ability to relate their theoretical knowledge with the case scenarios and they expressed confidence in their capacity to remember this knowledge due to their comprehensive understanding of the underlying principles. Conclusion: The implementation of online ECE has emerged as a timely and viable solution in response to the challenges posed by pandemic circumstances.